(untitled) (TRISANGAM INTERNATIONAL REFEREED JOURNAL, 2024)
After independence, questions arise about Indian nationalism. Pandit Jawaharlal Nehru said- ’The fundamental truth is that we have yet to build a united nation.’ The ruling class and other political representatives of India also knew that ’Indians are not one nation’. If we turn our eyes directly to Bengal, we see that as in ancient Bengal there were communities or tribes living in different townships, in modern Bengal too there was no lack of factions among Bengalis in terms of language, caste structure, caste etc. According to Niharranjan Roy, even though Bengali sense of homeland and patriotism arose in the ‘Pala period’ and this was accepted as the basis of Bengali homogeneity, we see that the ethnic discrimination of Bengali became extreme in the ‘Sena period’. Which was unbroken for a long time. Researchers have repeatedly drawn our attention to the similarities as well as contrasts with the Bengali, Marathi or Punjabi nations. As a result, the people of India were inspired by nationalism as ’one nation, one life’ against British colonialism - we have to stop at this thought. Imperialism amasses its financial, military, and administrative power mainly through the brokering of the bottom sections of society in the affected countries. This is equally applicable to Bengal and India. And this is where the differences start - ethnic, political, economic, class, religious, social and cultural. Then in manners, principles, the incompetent imitation of the British was taking place. Which is the main obstacle to the development of nationalism. When European civilization gives the highest importance to state interest in nationalism, lying, untruthfulness, deception do not seem shameful. But Rabindranath believed, ’Beyond caste religion there is a superior religion, which is of the Human being’. Several of his works testify to that. He did not want only a geographical India, he wanted a human India. The emotional product of this sense of difference is ’Gora’. In this novel of his, we find the main object of nationalism in ’bringing together the strange’. Which is the narrative of our main article.